A high-quality chromosome-level genome assembly of the mulberry looper, Phthonandria atrilineata - De-Long Guan; Ying-can Qin; Ya-Zhen Chen; Shi-Hao Zhang; Ji-ping Liu; Hui-Yu Yi; Xiao-Dong Li (Scientific Data, 2025)
Abstract The mulberry looper (Phthonandria atrilineata), a geometrid moth, plays a pivotal role in the destruction of mulberry trees (Morus spp.). In China, P. atrilineata is the most significant insect pest to sericulture, as it feeds on mulberry leaves and spreads diseases. The outbreak trend of P. atrilineata has been expanding yearly, causing substantial economic losses. Despite its ecological and economic importance, knowledge about the genomic background of P. atrilineata remains limited. Here, we report a chromosome-level reference genome of P. atrilineata, with a total size of 336.55 Mb, containing 15,026 protein-coding genes and 39.72% repeat sequences. These findings have the potential to shed light on the genetic basis of the destructive nature and environmental adaptation of P. atrilineata, offering valuable genomic resources for understanding genome evolution and pest management within this Lepidopteran pest.